Indonesia : Anatomy of a Banking Crisis Two Years of Living Dangerously 1997-99 - Kovanen, Arto (IMF Working Papers; Working Paper, 2001)
This study looks at the first two years of the banking crisis that erupted in Indonesia in late 1997. It finds that the banking sector was weak at the outset, and that governance problems intensified the crisis and seriously delayed its resolution. Although a strategy was put in place over the initial months, protracted delays in implementation led to an explosion in the costs of resolution. By end-1999, the critical elements to reconstruct the banking system were in place, and the political transition seemed completed; but, in a continuing unsettled environment, the new authorities still faced daunting challenges. This study looks at the first two years of the banking crisis that erupted in Indonesia in late 1997. It finds that the banking sector was weak at the outset, and that governance problems intensified the crisis and seriously delayed its resolution. Although a strategy was put in place over the initial months, protracted delays in implementation led to an explosion in the costs of resolution. By end-1999, the critical elements to reconstruct the banking system were in place, and the political transition seemed completed; but, in a continuing unsettled environment, the new authorities still faced daunting challenges. This study looks at the first two years of the banking crisis that erupted in Indonesia in late 1997. It finds that the banking sector was weak at the outset, and that governance problems intensified the crisis and seriously delayed its resolution. Although a strategy was put in place over the initial months, protracted delays in implementation led to an explosion in the costs of resolution. By end-1999, the critical elements to reconstruct the banking system were in place, and the political transition seemed completed; but, in a continuing unsettled environment, the new authorities still faced daunting challenges.